Equine osteoarthritis: An overview of different treatment strategies. - Elhussein Mahmoud (South Valley University, 2021)
Osteoarthritis (OA) has been considered the most common cause of lameness in equine, especially athletic horses. Different therapies are used for the treating of OA; hyaluronic acid (HA), a component of the articular cartilage matrix, has been shown to reduce OA-related lameness in horses. Recently, another biological therapy named platelet-rich plasma (PRP) is used for the treatment of OA. PRP consists of several growth factors which would be useful to inhibit the OA progression, till now, the obtained results of using either HA or PRP are still of contradictory effects on OA. Subsequently, one other novel alternative treatment option has been recently emerged in the veterinary field for treating musculoskeletal disorders. This novel treatment is known as stem cell therapy. In the present review, we explain different treatments of the OA such as HA, PRP, and stem cells therapy that would be effective to control lameness and locomotor disorders in equine.